2014
DOI: 10.1002/14651858.cd008758.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Extra fluids for breastfeeding mothers for increasing milk production

Abstract: Extra fluids for breastfeeding mothers for increasing milk production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…We found only five reviews examining the role of supplementation during lactation [ 7 , 79 82 ]. There was no conclusive evidence that zinc supplementation, polyunsaturated fatty acid supplementation nor MMN provided to breastfeeding mothers impacted infant health and growth outcomes [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found only five reviews examining the role of supplementation during lactation [ 7 , 79 82 ]. There was no conclusive evidence that zinc supplementation, polyunsaturated fatty acid supplementation nor MMN provided to breastfeeding mothers impacted infant health and growth outcomes [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is no clear evidence showing the impact of the amount of water intake in breastfeeding women on BM production [ 33 ]. A lack of well-conducted trials and the impact of hydration on BM production deserves further attention [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies concluded that lactating or pregnant women need to increase water intake to cope up with their physiological demands [ 39 ]. However, the effect of additional fluid intake, such as tea or coffee, is still unknown, due to insufficient systematic clinical/observational studies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%